Israel-Stewart Approach to Viscous Dissipative Extended Holographic Ricci Dark Energy Dominated Universe - Surajit Chattopadhyay (Advances in High Energy Physics)
This paper reports a study on the truncated Israel-Stewart formalism for bulk viscosity using the extended holographic Ricci dark energy (EHRDE). Under the consideration that the universe is dominated by EHRDE, the evolution equation for the bulk viscous pressure Π in the framework of the truncated Israel-Stewart theory has been taken as τΠ˙+Π=-3ξH, where τ is the relaxation time and ξ is the bulk viscosity coefficient. Considering effective pressure as a sum of thermodynamic pressure of EHRDE and bulk viscous pressure, it has been observed that under the influence of bulk viscosity the EoS parameter wDE is behaving like phantom, that is, wDE≤-1. It has been observed that the magnitude of the effective pressure peff=p+Π is decaying with time. We also investigated the case for a specific choice of scale factor; namely, a(t)=(t-t0)β/(1-α). For this choice we have observed that a transition from quintessence to phantom is possible for the equation of state parameter. However, the ΛCDM phase is not attainable by the state-finder trajectories for this choice. Finally it has been observed that in both of the cases the generalized second law of thermodynamics is valid for the viscous EHRDE dominated universe enveloped by the apparent horizon.